2022
DOI: 10.1096/fj.202201349rr
|View full text |Cite
|
Sign up to set email alerts
|

Twist2‐expressing cells reside in human skeletal muscle and are responsive to aging and resistance exercise training

Abstract: Skeletal muscle is maintained and repaired by sub-laminar, Pax7-expressing satellite cells. However, recent mouse investigations have described a second myogenic progenitor population that resides within the myofiber interstitium and expresses the transcription factor Twist2. Twist2-expressing cells exclusively repair and maintain type IIx/b muscle fibers. Currently, it is unknown if Twist2-expressing cells are present in human skeletal muscle and if they function as myogenic progenitors. Here, we perform a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Examination of skeletal muscle biopsy samples from young and elderly individuals showed that Tw2 + cells were more common in elderly muscles and increased after 12 weeks of resistance exercise training in humans. However, the number of Tw2 + cells is not related to muscle mass or myofiber CSA size, and their abundance is negatively correlated with CSA and myonuclear domain size after resistance exercise training [ 174 ]. This study shows that although Tw2 + cells respond to aging and exercise, their myogenic potential still needs further research.…”
Section: Other Interstitial Progenitor Cell Populationsmentioning
confidence: 99%
“…Examination of skeletal muscle biopsy samples from young and elderly individuals showed that Tw2 + cells were more common in elderly muscles and increased after 12 weeks of resistance exercise training in humans. However, the number of Tw2 + cells is not related to muscle mass or myofiber CSA size, and their abundance is negatively correlated with CSA and myonuclear domain size after resistance exercise training [ 174 ]. This study shows that although Tw2 + cells respond to aging and exercise, their myogenic potential still needs further research.…”
Section: Other Interstitial Progenitor Cell Populationsmentioning
confidence: 99%
“…Nevertheless, lineage tracing studies demonstrated that satellite cell activity is particularly high in the diaphragm under non-diseased conditions (33,34). In addition, there are likely interstitial stem cells that can contribute to myofibers that do not express PAX7 (50)(51)(52)(53). Future studies should determine the prevalence of non-satellite cell myogenic progenitors in the diaphragm of humans, and whether these cells are a significant source of myonuclei during diaphragm muscle homeostasis.…”
Section: Decreased Number Of Satellite Cells In the Mechanically Vent...mentioning
confidence: 99%